2020
DOI: 10.1007/s10620-019-06029-z
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Ascites Is Associated with Increased Mortality in Patients with Cirrhosis Secondary to Biliary Atresia

Abstract: Background Very few prior studies have investigated the presence of ascites as a prognostic factor in children with cirrhosis. To the best of our knowledge, there are no prior studies evaluating the relationship between severity of ascites and patient survival in children with biliary atresia and cirrhosis. Aims To evaluate the association between severity of ascites and survival of children with cirrhosis and biliary atresia. Methods All children with cirrhosis secondary to biliary atresia evaluated at our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…• Sodium restriction to 1-2 g/d to avoid excess salt intake to achieve negative sodium balance and fluid loss 5,7 • No specific recommendations for medical management for AKI-HRS • Single-center studies found use of terlipressin (as available) as continuous infusion with albumin showed improvement or stabilization in renal function 87,88 • Prioritization for urgent liver transplantation presence of ascites at the time of transplant listing is associated with enhanced waitlist mortality. 49,50,52 Children with BA and grade 3 ascites had 1-year survival of only 13.6% (HR: 17.3, p < 0.01) as compared with 97.1% in children without any ascites (p < 0.001). 50 This is even higher than previously reported HR of 2.59 (95% CI: 1.44-4.64, p ¼ 0.001) of ascites leading to increased mortality risk at 90 days after LT listing.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…• Sodium restriction to 1-2 g/d to avoid excess salt intake to achieve negative sodium balance and fluid loss 5,7 • No specific recommendations for medical management for AKI-HRS • Single-center studies found use of terlipressin (as available) as continuous infusion with albumin showed improvement or stabilization in renal function 87,88 • Prioritization for urgent liver transplantation presence of ascites at the time of transplant listing is associated with enhanced waitlist mortality. 49,50,52 Children with BA and grade 3 ascites had 1-year survival of only 13.6% (HR: 17.3, p < 0.01) as compared with 97.1% in children without any ascites (p < 0.001). 50 This is even higher than previously reported HR of 2.59 (95% CI: 1.44-4.64, p ¼ 0.001) of ascites leading to increased mortality risk at 90 days after LT listing.…”
Section: Managementmentioning
confidence: 99%
“…49,50,52 Children with BA and grade 3 ascites had 1-year survival of only 13.6% (HR: 17.3, p < 0.01) as compared with 97.1% in children without any ascites (p < 0.001). 50 This is even higher than previously reported HR of 2.59 (95% CI: 1.44-4.64, p ¼ 0.001) of ascites leading to increased mortality risk at 90 days after LT listing. 49 These findings support timely LT referral and evaluation in children who develop ascites.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a poor prognostic indicator, with only 50% surviving beyond two years. 2 , 3 Mortality worsens significantly to 20% to 50% at one year if the ascites becomes refractory to medical therapy. 4 Pakistan has one of the highest prevalence of viral hepatitis in the world and patients with ascites secondary to liver cirrhosis make a major percentage of both inpatient and outpatient burden.…”
Section: Burden Of Diseasementioning
confidence: 99%
“…Liver cirrhosis results from progressive replacement of normal parenchyma by fibrosis, nodule formation and the development of signs and symptoms of portal hypertension and organ failure. In children, the leading cause of cirrhosis requiring liver transplantation is biliary atresia 1 , 2 . Cirrhosis may also lead to manifestations in other organs, like heart 3 , lungs 4 , brain 5 , and kidneys 6 .…”
Section: Introductionmentioning
confidence: 99%